Manufacturing material effects : rethinking design and making in architecture - Kolarevic, Branko; Klinger, Kevin R. (New York : Routledge, 2008)
Innovative new techniques based on digital technologies are redefining the relationship between design and fabrication, enabling material explorations from the earliest states of design and throughout the production process. Leading designers, makers, and thinkers present their explorations.
Foreword : Prototyping architecture's future, again / Brett Steele --
Manufacturing/material/effects / Branko Kolarevic & Kevin Klinger --
Relations: information exchange in designing and making architecture / Kevin R. Klinger --
Material practice / SHoP Architects & Chris Sharples --
Innovation through accountability in the design and manufacturing of material effects / Ruben Suare --
Thinking versus making: remediating design practice in the age of digital representation / Phillip G. Bernstein --
Digitally defined manufacturing / L. William Zahner --
Fabricating material effects: from robots to craft-workers / Jeanne Gang --
Cut to fit / Frank Barkow --
Towards a digital materiality / Fabio Gramazio and Matthias Kohler --
The (risky) craft of digital making / Branko Kolarevic --
Computation and materiality / Marta Malé-Alemany and Jose Pedro Sousa --
Hox aesthetics: the restrained profligacy of second-order generative processes / Mark Goulthorpe --
Destiny of innovation : panel discussion --
Different differences / Donald Bates --
Opportunities of hybrid operations / David J. Lewis --
Translucencies / David Erdman --
Integral formation and materialization: computational form and material gestalt / Achim Menges --
Architectural CAD/CAM: pushing the boundaries of CNC fabrication in buildings / Fabian Scheurer --
Associative design in fabrication / Makai Smith --
Material experiments in design and build / Mick Eekhout --
OMAterial / Shohei Shigematsu --
Material collaborations / Marc Simmons --
Sensibilities and sensitivities : panel discussion.
ARC
Keywords: Architectural design; Building materials